2014
DOI: 10.1016/j.virol.2014.01.028
|View full text |Cite
|
Sign up to set email alerts
|

The DR6 protein from human herpesvirus-6B induces p53-independent cell cycle arrest in G2/M

Abstract: HHV-6B infection inhibits cell proliferation in G2/M, but no protein has so far been recognized to exert this function. Here we identify the protein product of direct repeat 6, DR6, as an inhibitor of G2/M cell-cycle progression. Transfection of DR6 reduced the total number of cells compared with mock-transfected cells. Lentiviral transduction of DR6 inhibited host cell DNA synthesis in a p53-independent manner, and this inhibition was DR6 dose-dependent. A deletion of 66 amino acids from the N-terminal part o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Although the role of the U14–p53 interaction remains unclear, it is possible that U14 induces the stabilization and functional inactivation of p53. Consistent with this, HHV-6 can induce cell-cycle arrest at G1/S or G2/M phase [ 20 , 21 , 22 , 23 , 24 , 25 ], and the HHV-6 DR6 protein has the ability to inhibit G2/M transition independently of p53 [ 31 ]; furthermore, HHV-6B U19 inhibits p53-dependent cell death [ 32 ]. Therefore, it is possible that U14 promotes cell-cycle arrest at G2/M independently of p53.…”
Section: Discussion/conclusionmentioning
confidence: 90%
See 1 more Smart Citation
“…Although the role of the U14–p53 interaction remains unclear, it is possible that U14 induces the stabilization and functional inactivation of p53. Consistent with this, HHV-6 can induce cell-cycle arrest at G1/S or G2/M phase [ 20 , 21 , 22 , 23 , 24 , 25 ], and the HHV-6 DR6 protein has the ability to inhibit G2/M transition independently of p53 [ 31 ]; furthermore, HHV-6B U19 inhibits p53-dependent cell death [ 32 ]. Therefore, it is possible that U14 promotes cell-cycle arrest at G2/M independently of p53.…”
Section: Discussion/conclusionmentioning
confidence: 90%
“…During HHV-6B infection, the majority of cellular p53 is inactivated and stabilized in the cytoplasm, most likely due to a reduction in p53 degradation [ 30 ]. Recent work showed that HHV-6 DR6 protein has the ability to inhibit the G2/M transition independently of p53 [ 31 ]. In addition, HHV-6B U19 inhibits p53-dependent cell death [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, TBP has been found to colocalize in the cell nucleus with the HHV-6B viral U94 [167] and DR6 proteins [168]. U94 is a latency associated protein described in section 1.1.3 and DR6 is a protein that delays cells in the G2/M-phase hence inhibit cell proliferation of host cells [169]. Also, TBP binding to DNA is increased during HHV-6B infection [168] and it is therefore highly plausible that the expressional increase observed in Study II is important in the HHV-6B biology.…”
Section: Study IImentioning
confidence: 99%
“…A new report showed that DR6 protein can induce accumulation of cells in G2/M and also the cytoplasmic accumulation of cyclin B1 [32 ]. This function was dependent on the N-terminal part of the protein, which is also required for nuclear localization.…”
Section: Cell Cycle Arrest In Roseoloviruses Infectionmentioning
confidence: 98%
“…HHV-6B infection led to cell cycle arrest in G1/S and/or G2/M depending on the cells that were tested [19,[29][30][31]32 ]. A new report showed that DR6 protein can induce accumulation of cells in G2/M and also the cytoplasmic accumulation of cyclin B1 [32 ].…”
Section: Cell Cycle Arrest In Roseoloviruses Infectionmentioning
confidence: 99%